Pengembangan Buku Foto Serangga Trilingual Sebagai Media Pembelajaran di Sekolah Alam Yombe Yawa Datum Kampung Wisata Rhepang Muaif, Nimbokrang, Kabupaten Jayapura - Ramandey, Euniche R.P.F.; Warikar, Evie L.; Ohee, Henderite L.; Heluka, Ina; Yansenem, Maya D. (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
The community project for developing a trilingual insect photo book aims to create a learning tool at Sekolah Alam Yombe Yawa Datum, Kampung Wisata Rhepang Muaif, Nimbokrang, Kabupaten Jayapura. This book is designed in three languages: Indonesian, English, and Namblong, with the goal of supporting nature-based learning and introducing students to the rich local biodiversity. The insect photo book not only facilitates the introduction of insect species found in the surrounding area but also serves as an innovative language learning tool. Through this development, students are expected to better understand the local ecosystem while improving their literacy in three languages. This project involves a collaborative process between teachers, students, and the local community and is integrated with outdoor field activities. The activities were carried out at Sekolah Alam Yombe Yawa Datum, involving 23 participants aged 6-16 years. The results of the project indicate that this trilingual book has had a positive impact on students' learning interest and has encouraged active participation in environmental and cultural preservation